Immune checkpoint inhibitors in osteosarcoma: A hopeful and challenging future - Zhang, Zeng; Tan, Xin; Jiang, Zengxin; Wang, Hao; Yuan, Hengfeng (Frontiers in Pharmacology, 2022)
Osteosarcoma (OS), the most common malignant tumor in the musculoskeletal system, mainly occurs in adolescents. OS results in high mortality and disability rates due to a fatal metastatic tendency and subsequent iatrogenic damage caused by surgery, radiotherapy and chemotherapy. Recently, immunotherapies have resulted in promising prognoses with reduced side effects compared with traditional therapies. Immune checkpoint inhibitors (ICIs), which are a representative immunotherapy for OS, enhance the antitumor effects of immune cells. ICIs have shown satisfactory outcomes in other kinds of malignant tumors, especially hemopoietic tumors. However, there is still a high percentage of failures or severe side effects associated with the use of ICIs to treat OS, leading to far worse outcomes. To reveal the underlying mechanisms of drug resistance and side effects, recent studies elucidated several possible reasons, including the activation of other inhibitory immune cells, low immune cell infiltration in the tumor microenvironment, different immune properties of OS subtypes, and the involvement of osteogenesis and osteolysis. According to these mechanisms, researchers have developed new methods to overcome the shortcomings of ICIs. This review summarizes the recent breakthroughs in the use of ICIs to treat OS. Although numerous issues have not been solved yet, ICIs are still the most promising treatment options to cure OS in the long run.